City of mosques: a collection of short stories - Alam, Shoaib, author; Becker, Leslee, advisor; Levy, E. J., committee member; Bernasek, Alexandra, committee member (Colorado State University. Libraries, 2016)
A collection of short stories exploring lives that begin or take root in Dhaka, the capital of Bangladesh. One of the major metropolises of the modern world, Dhaka is known in Bengal as the City of Mosques for its confluence of religion and culture, of past and present.